Role of veteran journalists and Influencers in the Promotion of fake news on social media: A Case of fake news in Pakistan - SHAHRYAR SHAIKH; Kaynat Azhar Satti; Zahra Sadiq (Journal of Peace, Development and Communication, 2024)
In today’s digital age, the dispersion of information has reached unaccustomed heights. Despite advancements in technology, a nefarious process has emerged, posing a threat to the trustworthiness of news sources and the reliability of information - fake news. The proliferation of fake news poses a significant challenge to societies worldwide, risking the foundations of democracy, impeding public converse, and sowing seeds of division. This study aims to explore the background and existence of fake news, the destructive consequences it entails, and the compelling need to combat this trouble, with a particular focus on recent developments in Pakistan. The objectives of this research are, to conduct a content analysis of fake news circulated by the three major political parties in Pakistan, to dissect the social media accounts of political actors/influencers to assess their involvement in spreading fake news, to perform sentiment analysis to understand the impact and blowout of the identified fake news stories, to give recommendations for combating the spread of fake news and enhancing media education in Pakistan.